Analytic hierarchy process applied on the stock exchange market: The Moroccan case - TAHIR , Samya; KADIRI, Abderrahim; ZARI , Tarek (Revue du contrôle, de la comptabilité et de l’audit, 2020)
The multitude of the stocks in a financial market could make the investors puzzled when it comes to taking a decision. Indeed, finding the best choice of stocks that would make a good investment could be a very difficult process. In order to solve this difficulty, many researchers and financial analysts have developed during the last decades several methods of stock selection in order to guide capital holders to the best investment strategy. This work based on the Analytic Hierarchy Process (AHP), which is a multicriteria decision making method, aims to classify publicly traded stocks on the Moroccan stock exchange from most to least interesting. First, a rigorous financial analysis will be performed for clearly identifying and carefully choosing ratios in order to use the maximum of information available on the shares. Then an empirical study will be established to provide a ranking of Moroccan companies by using AHP method, which would help investors to choose the most advantageous stocks.